Development of Knee Osteoarthritis in Older Age Women Patients - Mohammed Khalid Abbood; Hassanien Sagban Taghi; Zeyad Duraid Najmuldeen; Maysaa Ali Abdul Khaleq (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Knee osteoarthritis is a joint disorder that shows up essentially in elderly persons and is characterized by disintegration in the articular ligament, osteophyte, synovitis inflammation, and subchondral bone firmness. Knee osteoarthritis has numerous reasons, like age, presently solidly settled as a general medical issue. It is the most impairing illness in multiple nations. Knee osteoarthritis is viewed as the more typical type of ailment in a grown-up. Old ladies are seen as increasingly influenced by this ailment. From the accessible confirmations, it is currently sensible to consider this illness as one of the most significant among the interminable non-transferable maladies and examination for the hazard factors related to this issue is substantial. Aims: To describe the risk factors for developing symptomatic knee osteoarthritis in female Iraqi patients. Patients and Methods: This investigation incorporates 50 female patients with clinical and radiological highlights of knee osteoarthritis in different age groups. Result: The evaluated pervasiveness of knee osteoarthritis among women matured 40-49 years or more is 14 % of who had knee osteoarthritis with injury or trauma and 86% of women who had knee Osteoarthritis without injury or trauma. We additionally found that 94% of the ladies who experienced difficulty in doing daily schedule actions had a high increment in the levels of ESR, PLT, and CRP in serum. Conclusion: The elevation of knee osteoarthritis prevalence in female patients is because of the fact that most female patients develop knee osteoarthritis with aging. So that the quality of life of female patients in society will decline due to multiple factors affecting those women, with some high serum levels indicators